Distribution of epigaeic ants (Hymenoptera: Formicidae) across the transition between the Subantarctic and Patagonian subregions of the Andean region - Fergnani, Paula Nilda; Werenkraut, Victoria; Cuezzo, Fabiana; Ezcurra, Cecilia; Speziale, Karina; Ammassari, Luciana; Ruggiero, Adriana (Zootaxa, 2025)
We present comprehensive data including 32 ant species and 108,988 individuals, structured across the transition between Subantarctic and Patagonian subregions. This area encompasses one of the most pronounced environmental gradients in the world and represents the presence of local distributional limits for several ant species. Fifty sampling sites were located within an area of 150 km × 150 km, encompassing forests, shrublands, and steppes, and were sampled over 5 periods from November 2004 to March 2006. We included an occurrence matrix of species x sites, including catalogue numbers of the specimens housed in the biological collection of arthropods (BACRU) at the National University of Comahue, Centro Regional Universitario Bariloche. We also included the geographic position and environmental characteristics of the sites, and files in geospatial vector data format (“shapefiles”) for the local distribution of each species. We present an evaluation of sampling completeness and evenness. These data contribute to document biodiversity and may be useful for biogeographic analyses, diversity and conservation studies, and taxonomic analyses.